INDEPENDENT LEARNING STRATEGY OF NATURAL SCIENCE WITH â€œONE DAY ONE DIARY FOR SCIENCEâ€ PROGRAM - Herlianti, P. S.; Linuwih, S.; Dwijananti, P. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2015)
Learning behavior and metacognitive skill of students affect cognitive value and level of understanding of each student. The application of the